2012
DOI: 10.1038/nature11061
|View full text |Cite
|
Sign up to set email alerts
|

The let-7–Imp axis regulates ageing of the Drosophila testis stem-cell niche

Abstract: Adult stem cells support tissue homeostasis and repair throughout the life of an individual. During ageing, numerous intrinsic and extrinsic changes occur that result in altered stem-cell behaviour and reduced tissue maintenance and regeneration. In the Drosophila testis, ageing results in a marked decrease in the self-renewal factor Unpaired (Upd), leading to a concomitant loss of germline stem cells. Here we demonstrate that IGF-II messenger RNA binding protein (Imp) counteracts endogenous small interfering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(156 citation statements)
references
References 42 publications
6
148
1
1
Order By: Relevance
“…First, the data reported by Toledano et al (8) suggested that simply engrafting new or young stem cells into an old environment, such as the stem cell niche of an aged patient, may not lead to the optimal outcome regarding tissue regeneration and age-related conditions. Therefore, the stem cells themselves must be in an active state; however, the cells of the stem cell niche, other than the actual stem cells, must also be in a healthy and 'active' state and able to provide the proper signaling environment to maintain stem cell activity (17).…”
Section: Slowing the Aging Process Of Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the data reported by Toledano et al (8) suggested that simply engrafting new or young stem cells into an old environment, such as the stem cell niche of an aged patient, may not lead to the optimal outcome regarding tissue regeneration and age-related conditions. Therefore, the stem cells themselves must be in an active state; however, the cells of the stem cell niche, other than the actual stem cells, must also be in a healthy and 'active' state and able to provide the proper signaling environment to maintain stem cell activity (17).…”
Section: Slowing the Aging Process Of Stem Cellsmentioning
confidence: 99%
“…However, it is well-known that aging is associated with a progressive decline in stem cell function in various tissues (5). This age-related decrease in stem cell function is partially a consequence of the number of times the stem cell replicates (6), although it is also considered to be associated with intrinsic and environmental changes in the stem cell niche (7), such as a decrease of the self-renewal molecule Upd within the stem cell niche, leading to a lower number of active stem cells (8). Thus, during aging, as the environment deviates from the ideal, the gradual decline in stem cell function may lead to an impaired ability of self-healing and may be directly associated with certain diseases (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…It will lead to the development of strategies to treat age-onset diseases and facilitate stem-cell-based therapies in older individuals [183]. Further, there is an utmost need to have new reagents that could activate recruiting of intrinsic and extrinsic factors to induce or inject or implant progenitor cells into the damaged sites for repairing [184]. Individual tailored stem cells can be used for therapeutic purposes will be new innovative areas of future research [185,186].…”
Section: Future Clinical Prospectsmentioning
confidence: 99%
“…Testicular GSCs rely on signals from their niche, termed the germ cell hub [53]. An age-associated decline of IGF-II messenger RNA binding protein (IMP) that stabilizes the self-renewal signal Unpaired (Upd) on hub cells affects GSC aging [52,54]. Furthermore, older males express less DE-cadherin which reduces adhesion of GSCs to hub cells leading to age-related loss of GSCs [55].…”
Section: The Hsc Nichementioning
confidence: 99%